Whole exome sequencing reveals an FCGBP variant associated with spontaneous intraabdominal hemorrhage in severe acute pancreatitis - Qiu‐Yi Tang; Yue‐Peng Hu; Qi Yang; Jing Zhou; Jing‐Zhu Zhang; Jie Yang; Hai‐Bin Hao; Gang Li; Bai‐Qiang Li; Lu Ke; Zhi‐Hui Tong; Yu‐Xiu Liu; et al. (iMetaOmics)
Abstract This study investigated the genetic basis of spontaneous intraabdominal hemorrhage (SIH) in severe acute pancreatitis (SAP) to facilitate the development of more effective treatments for this life‐threatening complication. A four‐phase study was conducted with a large cohort of acute pancreatitis (AP) patients (n = 600). In the first phase, whole‐exome sequencing identified a specific exonic variant (rs1326680184) in the human Fc gamma binding protein (FCGBP) gene consistently associated with SIH. The second phase employed serum ELISA tests, revealing that this variant altered FCGBP protein levels, increasing susceptibility to SIH. In the third phase, functional validation was performed through: (i) in vivo experiments using a Fcgbp‐knockdown mouse model demonstrated that reduced Fcgbp expression exacerbated AP severity and increased the risk of hemorrhage; and (ii) in vitro experiments with FCGBP‐knockdown in human vascular fibroblasts showed that decreased FCGBP expression destabilized the vascular wall, leading to vascular injury in SAP. Finally, the fourth phase compared clinical characteristics of FCGBP rs1326680184 carriers and non‐carriers, finding that carriers exhibited higher risks of severe complications, worse AP prognosis, and demonstrated enhanced diagnostic utility as a predictive indicator. These findings provide critical insights into the genetic basis of SIH in SAP, paving the way for precision therapies and effective prognostic tools to improve AP management and early intervention.